Fish Catch Results Related to Temperature and Chlorophil in Western Waters of Sumatera - Ewin Handoco S; Ria Retno Manik; Jogi Arleston (Politeknik Negeri Batam, 2022)
The western waters of Sumatera are one of the waters that have the potential of coastal and ocean resources. Oceanographic factors that can be related to high productivity in waters are SST (Sea Surface Temperature) and the distribution of chlorophyll concentration. Sibolga waters are geographically quite strategic, because they are located in the Indian Ocean, most of the catch is landed at the Sibolga Nusantara Fisheries Port. This Study aims to understand the trend of fluctuations in fish catches in the The Waters of Western Sumatera, to examine the effect of chlorophyll on fish catches in the waters of West Sumatera. Sea surface temperature and monthly chlorophyll-a concentrations were obtained from the result of the Aqua Modis months in 2021. Monthly data and data on fishing results were obtained from the Sibolga Nusantara Fisheries Port. The composition of catches in the western waters of Sumatera which landed at PPN Sibolga in 2021there three dominant fish species, namely Cakalang (Katsuwonis Pelamis) 11.655.768 Kg, Layang (Decapterus Sp) 4.589.147 (19,95%), Tembang (Sardinella sp) 2.421.523 (10,53%), the variation of fish catch per unit (CPUE) ;anded at PPN 2021. The Highest occurred in may at 3.809 kg/trip and the lowest occurred in November 1.521,58 kg/trip and the average monthly CPUE in 2021 was 5.105,88kg/trip. Monthly variations of sea surface temperature and chlorophyll-a in the waters of for 12 months (2021) the lowest temperature occurred in August, namely 26,88 0C while the highest temperature in February was 30,92 0C, the highest consentration was in May of 1,56 mg/m3 while the lowest occurred in March at 0,15 mg/m3.